Blended Learning in Bachelor’s Nursing Education: Exploring Student Experiences, Satisfaction, and Knowledge - Abusabeib ZA (Advances in Medical Education and Practice)
Zeinab A Abusabeib Department of Community and Psychiatric Mental Health Nursing, College of Nursing, Princess Nourah bint Abdulrahman University, Riyadh, 11671, Saudi ArabiaCorrespondence: Zeinab A Abusabeib, Email zaabusabeib@pnu.edu.saBackground: Blended learning merges in-person instruction with online education, offering flexible and individualized learning experiences. This approach is especially valuable in nursing education, where connecting theoretical knowledge with practical application is crucial.Objective: The study aims to investigate nursing students’ experiences and satisfaction levels regarding blended learning in a Clinical Nutrition Course targeted at third-year nursing students while comparing the knowledge outcomes of blended learning and traditional learning groups.Methods: A cross-sectional study design was utilized to evaluate the experiences of 307 female nursing students through the Web-based Learning Environment Instrument (WEBLEI). Data were collected online using a 5-point Likert scale and analyzed with descriptive statistics. Moreover, academic performance between the blended learning group (2024– 2025) and the traditional group (2023– 2024) was compared using independent t-tests.Results: Students reported a high level of satisfaction with blended learning, evident from the overall WEBLEI scores. Scores for Access (4.48), Interaction (4.40), Response (4.59), and Results (4.64) indicated favorable views regarding flexibility, engagement, and knowledge gain. The blended learning group exhibited significantly better academic performance (Total Score: 94.39 ± 4.78) compared to the traditional group (89.21 ± 5.39; p < 0.001).Conclusion: Blended learning significantly improves both student satisfaction and academic performance in nursing education. Enhancing peer interaction and incorporating additional synchronous activities could further enhance the blended learning approach.Keywords: blended learning, nursing education, student satisfaction, academic performance